Prevalence of Poultry Coccidiosis and Associated Risk Factors in Intensive Farming System of Gondar Town, Ethiopia - Anteneh Wondimu; Ermias Mesfin; Yehualashet Bayu (Veterinary Medicine International)
A cross-sectional study was conducted from November 2018 to April 2019 in Gondar town, Ethiopia, with the objectives to determine the prevalence of coccidiosis and to assess the associated risk factors. The floatation technique was used for isolation of coccidian oocysts obtained from 384 fecal samples of chicken, and the prevalence revealed was 42.2%. The result showed 43.6% of male and 41.2% female chickens found infected with Eimeria. From the examined chickens, higher degree of infection was observed in the younger age group (51.0%) than adult chickens (36.7%). The difference was statistically significant (p<0.05). The study showed relatively higher prevalence in poor body condition chickens (72.6%) than medium (36.1%) and good body condition (30.5%) with statistically significant difference (p<0.05). The result also showed higher prevalence of coccidiosis in the floor system (50.4%) than in the cage system (19.0%), and the difference was statistically significant (p<0.05). The prevalence based on the management system was 63.7%, 39.4%, and 29.3% in poor, medium, and good management, respectively. Significant difference was seen in the prevalence of poultry coccidiosis, between poorly and properly managed chickens (p<0.05). In addition, the study reported 46.1%, 36.7%, and 26.3% prevalence in Bovan Brown, White Leg Horn, and Rhode Red Island chicken breeds, respectively. Coccidiosis is a major problem in the farm with inadequate hygienic measures and factors such as age, breed, body conditions, and biosecurity which are the most common factors that contribute for the occurrence of coccidiosis. Therefore, appropriate control strategies should be designed considering important risk factors such as, breed, age, management system, and housing system. Especially, focus should be given to biosecurity practices in the prevention and control of coccidiosis, and in addition, further studies are needed to be conducted to identify the prevalent Eimeria species for strategic control.